Spontaneous Per Oral Explantation of Intragastric Balloon—A Case Report - Karthik, Somu; Shah, Aashish R.; Ravishankar, K. S.; Jan, Nawab (Journal of Digestive Endoscopy, 2019)
Obesity is a modern-day pandemic that was once a disease of only the affluent Western world. However, over the years it has achieved a global footprint. The need to treat obesity with nonsurgical means in patients who do not qualify or refuse bariatric surgery or in some patients as a bridge to surgery is all the more relevant now. It is for this subset of patients that a modality like the intragastric balloon holds promise. Previously reported complications of the balloon include esophagitis, severe nausea and vomiting, abdominal cramps, hiccoughs, belching, intestinal obstruction, gastric perforation, pancreatitis, and aspiration.1 Balloon rupture/leak leading to intestinal migration and obstruction has been managed by surgical intervention. Review of literature did not reveal any report of spontaneous per oral explantation of the deflated balloon. We are reporting a case of the same.
Keywords: intragastric balloon; complications; per oral explantation